2011
DOI: 10.4236/fns.2011.21002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Dietary Lipids on Growth Performance, Digestibility, Fatty Acid Composition and Histology of African Catfish (Heterobranchus longifilis) Fingerlings

Abstract: The present study was performed to investigate the influence of fish oil (FO), two terrestrial animal fats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…Total n-3 content was higher in many farm-raised fillets than wild-caught fillets, but the difference was not as dramatic as it was with other fatty acids. This is most likely due to the higher costs associated with diets high in n-3 fatty acids, which are derived from fish oils [41,42]. Because of the additional costs associated with diets high in n-3 fatty acids, they are often incorporated into the diet late in the lifetime of farmed fish [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total n-3 content was higher in many farm-raised fillets than wild-caught fillets, but the difference was not as dramatic as it was with other fatty acids. This is most likely due to the higher costs associated with diets high in n-3 fatty acids, which are derived from fish oils [41,42]. Because of the additional costs associated with diets high in n-3 fatty acids, they are often incorporated into the diet late in the lifetime of farmed fish [43].…”
Section: Discussionmentioning
confidence: 99%
“…For wild-caught species, the diet is determined by changes in environmental conditions, while the composition of farmed species is dependent upon the amount and composition of the feed [32]. In order to control costs, diets high in inexpensive and readily available fatty acids, like SFA, MUFA, and n-6 obtained from plant or animal sources, are often used in aquaculture [41,42]. Although the fillets analyzed in this study were obtained from Trout,Rainbow (1,9;8,20) Bass, Striped (5, [31] is also shown.…”
Section: Discussionmentioning
confidence: 99%
“…The lowering of linolenic acid in fish muscle lipids compared to initial might be due to the low amounts of this fatty acid in trial diets. Indeed, the fatty acids of muscle lipids in African catfish reflected the fatty acid profile of the dietary oil that was fed (Ng et al 2003;Babalola et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fish feed alone account for between 60 and 75% of the total cost of fish production (Babalola 2010). Thus, aquaculture production can be profitable only if the operators have access to balanced food at competitive prices (FAO 2016) by using locally available inputs.…”
mentioning
confidence: 99%
“…Fish oil is an excellent lipid source in commercial aquaculture feeds for provision of energy and essential fatty acid (EFA) (Babalola, Apata, Omotosho, & Adebayo, ; Seyedvali et al., ). However, due to its high cost, limited supply and high risk of oxidation, many researchers have dedicated to examine the substitution of fish oil with vegetable oils in the past decades (Babalola et al., ; Dosanjh, Higgs, Plotnikoff, Markert, & Buckley, ; Francis, Turchini, Jones, & De Silva, ; Rosenlund, Obach, Sandberg, Standal, & Tveit, ). Dietary oil is known as a concentrated and highly digestible source of energy and also supplies animals with EFA for normal growth and development.…”
Section: Introductionmentioning
confidence: 99%